INVESTIGATION OF STUDENT SATISFACTION TOWARD HIGHER EDUCATION INSTITUTION: EMPIRICAL EVIDENCE FROM UNIVERSITAS TEUKU UMAR - Zainal Putra; Cut Devi Maulidasari; Muzakir Muzakir; Mimin Suriadi (Universitas Serambi Mekkah, 2019)
The purpose of this research is to measure the student satisfaction in Universitas Teuku Umar and to measure the suitability level between performance and costumer interest by using importance performance analysis method. The result of the research shows that the overall score of student satisfaction is 73,92 with quality level of ‘C”, category of “less good”. Based on each element, there are 12 elements that achieved quality of ‘B’, category of ‘Good’. There are 51 elements that achieved the quality of ‘C’, Category of ‘Less Good’. The analysis results by using importance performance analysis shows that there are 10 attributes which falls into quadrant A or red zone, namely: attribute 11, attribute 13, attribute 15, attribute 22, attribute 23, attribute 25, attribute 27, attribute 48, attribute 62 and attribute 63. This quadrant shows that the interest level is high, however the performance is low. This is the main weakness; therefore, it requires attention from the management.